Surgery-Related Quality of Life of Pediatric Patients With Crohn's Disease - Dipasquale, Valeria; Antonelli, Enrica; Cannavò, Laura; Cavatoi, Giorgio; Romeo, Carmelo; Trimarchi, Giuseppe; Navarra, Giuseppe; Romano, Claudio (Frontiers in Pediatrics, 2020)
Objective:Up to 30% of pediatric patients with Crohn’s disease (CD)require surgery. The aim of the study was to evaluate long-term health-related quality of life (HRQoL)outcome in children with CD who have had ileocolonic resection. Materials and methods:This was a retrospective cross-sectional study on all pediatric patients who had undergone surgery for CD between January 2015 and December 2017 in the Pediatric Surgery and Gastroenterology Units of the University Hospital of Messina. Surgical treatment was represented by laparoscopic ileocecal resection with latero-lateral anastomosis. Patients were asked to fill in a modified version of the IMPACT III questionnaire made up of 15 closed questions before and after surgery. The questionnaire was scored on a five-point scale with 5 reporting “not a problem” and 1 “a very severe problem”. The total score ranged from 15 (worst HRQoL) to 75 (best HRQoL). Frequency of relapses, reoperations, complications during follow-up, and postoperative bowel function were also studied. Results:Data were obtained in 10 patients (9 males), who underwent surgery at a median age of 13.5 years (range 13-18), after a median post-diagnosis period of 2.5 years (range 0-8). Preoperative scores were low in all 4 domains of the questionnaire. Postoperatively, HRQoL measures improved significantly (p<0.05) about symptoms, school attendance, social and emotional functioning. Overall, nearly all patients were completely satisﬁed with the surgical outcome. Conclusions:HRQoL is low in CD children referred for possible operation, and surgery may positively affect the overall HRQoL. Collecting HRQoL data provides insight into the impact of treatment on children health status.